Action learning: ripples within and beyond the set. Issue 2 (2nd May 2017) - Warwick, Robert James; Palmer, Adam; McCray, Janet
Abstract : Purpose: This paper aims to explore the impact of action learning (AL) on an individual and an organisation, particularly the process by which each affected the other. The organisation is a UK National Health Service (NHS) Trust that includes two hospitals. Design/methodology/approach: This is a single person case study involving a clinician, but the voice of an author can also be heard. It involves the experience of the individual as they experience AL as part of a leadership development programme leading to a postgraduate certificate. The authors explain their caution of the case study approach and in doing so offer their thoughts in how this paper could be read and impact on practice. Findings: The authors show a process whereby an AL set participant moves from being confident about their project to one of uncertainty as the impact of the project ripples throughout the organisation. Through this process of unsettlement, the individual's unnoticed assumptions are explored in ways that enable practical action to be taken. In doing so, the individual's leadership and identity developed. Research limitations/implications: This is a single person case study in one organisation, thus affecting wider generalisation. Originality/value: This single case study contributes to the debate on critical AL and the use of AL in the NHS.